Determination of Thermal Behavior from Core Flux Density with Image Processing Technique for Distribution Transformers - Aslan, Busra; Balci, Selami; Kayabasi, Ahmet (International Journal of Applied Methods in Electronics and Computers, 2024)
Considering the design and operating conditions of transformers, electromagnetic and mechanical stresses cause aging and negatively affect their operating performance. Advanced fault diagnosis methods have been developed based on information system-based remote online monitoring or electrical data obtained from sensors or sample windings added to the transformer core. The electromagnetic field distribution in the core structure of the transformer can respond quickly and effectively to fault situations. Therefore, changes in flux density within the core can be analyzed using image processing and/or data analysis methods. In this study, electromagnetic modeling of a distribution transformer with nominal values of 34.5/0.4 kV and 2000 kVA was conducted using Finite Element Analysis (FEA) software. Image processing techniques were applied to observe the behavior of the flux distributions on the core when the transformer was under nominal sinusoidal voltage. Then, considering the effect of the flux distribution in the core on the thermal state of the transformer, the thermal behavior of the core was derived with mathematical equations and shown on the transformer. Thus, the flux distribution in the core of a distribution transformer operating under nominal power conditions was examined and, a novel approach based on simulation studies was proposed to determine the flux distributions and thermal behavior of the transformer under fault conditions.